2019
DOI: 10.1111/apha.13257
|View full text |Cite
|
Sign up to set email alerts
|

Investigating brain d‐serine: Advocacy for good practices

Abstract: The last two decades have witnessed remarkable advance in our understanding the role of D-amino acids in the mammalian nervous system: from the unknown, to known molecules with unknown functions, to potential central players in health and disease. D-Amino acids have emerged as an important class of signaling molecules. In particular, the exploration of the roles of D-serine in brain physiopathology is a vibrant field that is growing at an accelerating pace. However, disentangling the functions of a chiral mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…Thus, the oral ingestion of madecassoside can reduce the production of neuronal D-serine. Although the usage of glutaraldehyde crosslinked antibody has some reservation in case of solid tissues, the cultured-neurons in our experiments have displayed a similar punctate distribution of D-serine in neurons that have been reported earlier 64 .…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the oral ingestion of madecassoside can reduce the production of neuronal D-serine. Although the usage of glutaraldehyde crosslinked antibody has some reservation in case of solid tissues, the cultured-neurons in our experiments have displayed a similar punctate distribution of D-serine in neurons that have been reported earlier 64 .…”
Section: Discussionsupporting
confidence: 79%
“…Finally, implantable biosensors and surface-scanning biosensors will offer innovative tools for future research aimed at investigating the neurological role of D-AAs, a vibrant field that is growing at an accelerating pace. In past years, considerable progress in understanding D-AAs biology has been made, but the determination of these molecules constitutes a challenging task that can confound observations: we encourage the use of appropriate procedures with multiple controls, as recently suggested by [ 100 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…While SR catalyses the synthesis of D-serine, both SR and DAAO can mediate its degradation. 1 In ischemia/reperfusion injury (IRI) model in mice, Sasabe et al demonstrated that knock out of SR in mice reduced the basal level of D-serine. However, no alteration of serine enantiomers ratio was observed.…”
Section: D-serine Synthesis and Degradationmentioning
confidence: 99%
“…3 Measurements of D-enantiomers are challenging because they share the same physical properties with the L-enantiomers. 1 Mothet et al emphasized the importance that researchers validate the specificity of their detection through suitable controls. 1 Nowadays, 2D high-performance liquid chromatography (HPLC) is one of the methods of choice for a precise measurement of D-amino acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation